Transformation of the Traditional Power of Kazakhs in the Russian Empire (on the example of the Kazakhs of the Orenburg Department) - Yermenbayeva, Gulzhan; Balgabayeva, Gaukhar; Isenov, Otegen; Nauryzbayeva, Elmira (Bylye Gody, 2017)
On the basis of the legislation studying of 20–40th years of the XIXth century and taking into account new theoretical and methodological approaches, the issue of the traditional nomad system’s transforming of the management by the Kazakhs of Orenburg administration in the first half of the XIXth century is considered in the article. The administrative-territorial reforms provided the functioning of the new system of management. The highest stage in the system of military and administrative management by the Kazakh population belonged to Russian State administration, represented by Orenburg governor general and Orenburg boundary commission in the field. The position of the sultan-ruler was classified to the structure of the middle-level authority, distance and aul chiefs, which were represented by the Kazakh people, to the low-level. The liquidation of Khan authority as a consequence of the consistent promotion of Russian structure of the authority in the extensive region led to a substitute of the traditional form of management by the nomads of new system of the administrative-territorial management. There were peculiar symbiosis of traditional nomad and Russian system of the political management by the society and definite merging of two heterogeneous political cultures.
Keywords: Orenburg governor general; boundary commission; traditional authority; administrative-territorial reform; Young Zhuz; khan's authority; sultan-ruler; distance; distance head; local (aul) chief